Situation of Tularaemia in Spain in 2022. A five-year context overview (2018-2022) (Boletín Epidemiológico Semanal, 2023)
Introduction: Tularaemia is a zoonosis caused by Francisella tularensis. It is a virulent agent that affects humans and a wide range of animal species, surpassing any other known zoonotic microorganism. The objective was to describe the epidemiology of reported tularemia cases in Spain in 2022 in relation to the previous period (2018-2022).Method: A descriptive analysis of autochthonous tularaemia cases in Spain from 2018 to 2022 was performed by using the notifications to the Spanish National Epidemiological Surveillance Network (RENAVE). The variables analysed were sex, age in ten-year age groups, Autonomous Community (AC) of residence, AC of exposure, and case classification (probable or confirmed).Results: During the period 2018-2022, 227 cases of tularaemia were reported (incidence rate per 100,000 population IR = 0.09). There was a notable increase in IR in the year 2019 (IR= 0.40) due to an outbreak in Castilla y León. The number of cases was higher in men throughout the entire period, and consequently, the IR. The age group with the highest IR was 50-59 years (IR= 0.18).Conclusions: In the studied period, specifically in the year 2022, most cases were detected in men aged 40 to 60 years. The significant increase in cases in 2019, with more than 90% of the total cases reported, was due to the outbreak in Castilla y León. It is essential to maintain efforts to control the disease and implement preventive measures to avoid future outbreaks.
Keywords: Tularaemia; Francisella tularensis; One Health; Epidemiological surveillance